Aktivitas Sedatif Kombinas Ekstrak Putri malu (Mimosa pudica) dan Kayu secang (Caesalpinia sappan L) pada Mencit (Mus musculus) - Panji Ratih Suci; Revi Syahrin A (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Insomnia is a common sleep disorder. Insomnia can be managed with the use of sedative-hypnotic drugs, however, long-term use and specific dosages can lead to dangerous side effects. Therefore, alternative treatments utilizing natural substances such as Mimosa pudica and Caesalpinia sappan are needed. This study utilized 25 randomly divided mice into 5 groups. Diazepam was used as the positive control (+), aquadest and agar as the negative control (-), the group Extract MP (Mimosa pudica), Extract CS (Caesalpinia sappan), and the combination of Extract MP+CS (24mg/kgBW). Administration of the suspension was done orally via gastric lavage. The conclusion drawn from this study is that ethanol extracts of Mimosa pudica (MP), Caesalpinia sappan (CS), and their combination (MP+CS) at a dosage of 24 mg/kgBW exhibit sedative effects. Their effects and combination are comparable to standard synthetic drugs.